(untitled) (Canadian Dermatology Today, 2022)
Antihistamines are medications that are used by dermatologists for the labelled indications of urticaria and IgE mediated allergies. They may also be used off-label for conditions including, but not limited to, mast cell-mediated diseases and pruritus of any type. With so many antihistamines available in Canada, it can be hard to choose which one to recommend or prescribe. With a focus on oral H1 antihistamines, the ones primarily used in dermatology, this review will explore and provide a practical overview to help physicians select ideal antihistamines for each patient based on their similar and unique characteristics.